2009
DOI: 10.1021/jf903040z
|View full text |Cite
|
Sign up to set email alerts
|

Use of Methanol for the Efficient Extraction and Analysis of Melamine and Cyanuric Acid Residues in Dairy Products and Pet Foods

Abstract: The recent worldwide shortage of acetonitrile has prompted the development of a new method using methanol as an alternative organic solvent in the extraction and liquid chromatographic analysis of melamine and cyanuric acid that may be present as contaminants in dairy products and pet foods. A simple extraction of melamine and cyanuric acid residues in fortified samples was successfully achieved, using a methanol-water mixture and analysis by isotopic dilution high-performance liquid chromatography-triple-quad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 10 publications
0
22
0
1
Order By: Relevance
“…Several methods have been reported for the analysis of CA in swimming pool water, such as gas chromatography (GC), 6 gas chromatography-mass spectrometry (GC-MS), 7 liquid chromatography (LC), 1,3,8 liquid chromatography-mass spectrometry (LC-MS) [9][10][11][12][13] and ion-pair LC. 14 There has been no report about the determination of CA by ion chromatography (IC).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been reported for the analysis of CA in swimming pool water, such as gas chromatography (GC), 6 gas chromatography-mass spectrometry (GC-MS), 7 liquid chromatography (LC), 1,3,8 liquid chromatography-mass spectrometry (LC-MS) [9][10][11][12][13] and ion-pair LC. 14 There has been no report about the determination of CA by ion chromatography (IC).…”
Section: Introductionmentioning
confidence: 99%
“…Acetonitrile has the characteristics of miscibility with water, low viscosity and results in protein denaturation which is useful in food or feed preparation to eliminate protein in the sample solution. Some studies have also reported using 30-50% methanol to reduce the amount of acetonitrile combined with sonication or two step centrifugation to extract the MEL in liquid formula, dry powder or pet foods (Tran et al, 2010;Vendatasami & Sowa Jr 2010). In addition, the non-polar solvents dichloromethane and hexane are used in lipid-lipid extraction to reduce lipid effects in highfat bio-samples, such as animal-derived food or bakery goods.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The optimal harmonized method must be easyto-use, economical in time and cost, and must cause no harm to the environment and analyst. For determining either MEL alone or with related analogues, previous HPLC techniques combined with UV [6], photo-diode array detector (PDA) [7], and LC-MS/ MS [8][9][10][11] have been reported. The US Food and Drug Administration issued new methods for the analysis of melamine in liquid formula, based on LC-MS/MS detection [12].…”
Section: Introductionmentioning
confidence: 99%